2016
DOI: 10.1186/s12879-016-2058-1
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of hepatic microRNA expression profiles with Clonorchis sinensis infection

Abstract: Background: Clonorchiasis remains an important zoonotic parasitic disease worldwide. The molecular mechanisms of host-parasite interaction are not fully understood. Non-coding microRNAs (miRNAs) are considered to be key regulators in parasitic diseases. The regulation of miRNAs and host micro-environment may be involved in clonorchiasis, and require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Because of the limited commercially available antibodies or probes, it is not appropriate for evaluating the pathogenesis or immune responses in hamsters ( Uddin et al, 2012 ). Although the rats develop resistance to reinfection by C. sinensis ( Quan et al, 2005 ), with the advantages of small size, low cost, wide source, easy feeding, and suitable for large-scale observation, rats have been broadly used as animal models for exploring pathogenesis of clonrochiasis ( Choi et al, 2004 ; Quan et al, 2005 ; Sohn et al, 2006 ; Han et al, 2016 , 2017 ). In addition, we could get better adults recovery rates and development of worms in rats models.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the limited commercially available antibodies or probes, it is not appropriate for evaluating the pathogenesis or immune responses in hamsters ( Uddin et al, 2012 ). Although the rats develop resistance to reinfection by C. sinensis ( Quan et al, 2005 ), with the advantages of small size, low cost, wide source, easy feeding, and suitable for large-scale observation, rats have been broadly used as animal models for exploring pathogenesis of clonrochiasis ( Choi et al, 2004 ; Quan et al, 2005 ; Sohn et al, 2006 ; Han et al, 2016 , 2017 ). In addition, we could get better adults recovery rates and development of worms in rats models.…”
Section: Disscusionmentioning
confidence: 99%
“…Notably, C. sinensis has been classified as a Class I carcinogen by the International Agency for Research on Cancer ( Grosse et al, 2009 ). Our previous research had found that C. sinensis infection induced the dysregulation of hepatic microRNA and hepatic apoptosis in rat models ( Zhang et al, 2008 ; Han et al, 2016 ). However, the molecular pathogenesis of clonorchiasis is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor metastasis is a multi-step, multi-stage and multipathway complex process, which includes the detachment of tumor cells from the primary lesion, invasion into blood vessels or lymph vessels, migration and adhesion to appropriate sites, induction of tumor angiogenesis, anti-host antitumor immunity, and the eventual formation of distal metastasis (4). Multiple genes are involved during this process.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C. sinensis has been classified by the International Agency for Research on Cancer (IARC) as a group 1 biocarcinogen in humans [ 3 ]. The main mechanism for hepatic and biliary damage is that the flukes migrate through the biliary system and they secrete or excrete metabolic products, which result in immunopathogenesis and simultaneous liver injury [ 4 , 5 ]. However, the mechanism underlying hepatic and biliary damages in hosts has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%